1970
DOI: 10.1038/bjc.1970.51
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Betel-Nut Chewing on the Buccal Mucosa: A Histological Study

Abstract: SUMMARY.-Sixty-two " leukoplakias " from the cheeks of betel-nut chewers in West Malaysia were studied histologically. Ten biopsies were from nontobacco betel-nut chewers. An amorphous von Kossa positive layer was seen on the keratin surface in 42 specimens. Tobacco did not appear essential for its formation, and it appeared to be significantly associated with parakeratosis. Its possible significance as a cuticle-like layer prolonging contact between carcinogens and the mucosa is discussed.Parakeratosis appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
(5 reference statements)
2
10
0
Order By: Relevance
“…Development of resistance to terminal differentiation stimuli is a key event in carcinogenesis, as evident from experimental data (Cerutti, 1988;Harris, 1991) and from abnormal differentiation patterns in human tumors, including those of oral origin (Eisenberg et a/., 1987). Betel quid chewing is also associated with abnormal differentiation patterns, as demonstrated by the common findings of hyperkeratosis, hyperplasia and acanthosis (Reichart et al, 1984;Tennekoon and Bartlett, 1969;Lee and Chin, 1970). In this study, an increase in involucrin expression was found after exposure to the extract in normal buccal epithelial cells, but not in SqCCiYl cells, which are also resistant to endogenous differentiationinducing agents (Sundqvist eta/., 1 9 9 1~) .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Development of resistance to terminal differentiation stimuli is a key event in carcinogenesis, as evident from experimental data (Cerutti, 1988;Harris, 1991) and from abnormal differentiation patterns in human tumors, including those of oral origin (Eisenberg et a/., 1987). Betel quid chewing is also associated with abnormal differentiation patterns, as demonstrated by the common findings of hyperkeratosis, hyperplasia and acanthosis (Reichart et al, 1984;Tennekoon and Bartlett, 1969;Lee and Chin, 1970). In this study, an increase in involucrin expression was found after exposure to the extract in normal buccal epithelial cells, but not in SqCCiYl cells, which are also resistant to endogenous differentiationinducing agents (Sundqvist eta/., 1 9 9 1~) .…”
Section: Discussionsupporting
confidence: 58%
“…Betel quid chewing is also associated with abnormal differentiation patterns, as demonstrated by the common findings of hyperkeratosis, hyperplasia and acanthosis (Reichart et al, 1984;Tennekoon and Bartlett, 1969;Lee and Chin, 1970). In this study, an increase in involucrin expression was found after exposure to the extract in normal buccal epithelial cells, but not in SqCCiYl cells, which are also resistant to endogenous differentiationinducing agents (Sundqvist eta/., 1 9 9 1~) .…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…As seen in Table 2, all but two vitamin A controls show hyperorthokeratosis and only two show parakeratosis. In both rodent and human epithelium, keratinizalion occurs in response to trauma, be it inflicted artificially (Dunham & Herrold 1962, Dunham et al 1966, Sirsat & Kandarkar 1968 or in the course of addictive exposure to the ingredients of the betel chew (Sirsat & Doctor 1967, Lee & Chin 1970, Sirsat et al 1974. This marked provocation of anomalous keratinization by the test substances makes it difficult to judge effectively the role of superimposed vitamin A on the enhancement of this epithelial morbidity.…”
Section: Discussionmentioning
confidence: 99%